2005
DOI: 10.1021/jm050765n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Cyclic Secondary Amine Substituted Phenyl and Benzyl Nitrofuranyl Amides as Novel Antituberculosis Agents

Abstract: In an ongoing effort to develop new and potent antituberculosis agents, a second generation series of nitrofuranyl amides was synthesized based on the lead compound 5-nitro-furan-2-carboxylic acid 3,4-dimethoxy-benzylamide. The primary design consideration was to improve the solubility and consequently bioavailability of the series by the addition hydrophilic rings to the benzyl and phenyl B ring core. The synthesis of 27 cyclic, secondary amine substituted phenyl and benzyl nitrofuranyl amides is described an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 22 publications
1
41
0
3
Order By: Relevance
“…In an effort to develop new and more potent therapies to treat TB, a novel class of anti-infectives with high in vitro activity against M.tb, nitrofuranylamides, has recently been characterized by our group (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to develop new and more potent therapies to treat TB, a novel class of anti-infectives with high in vitro activity against M.tb, nitrofuranylamides, has recently been characterized by our group (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…With the same interest, the efficacy of anti-TB, 5-nitrofuranylamides NFAs (29a-e) against TB complex and other clinically relevant nonmycobacterial species [51] and found that the NFAs were significantly active against Mtb complex [52][53][54][55]. Compound 29a showed preeminent inhibition of MIC 0.006 mg/L against Mtb UT30 (streptomycin resistant at 4 mg/L).…”
Section: Piperazine and Pyrazine Derivativesmentioning
confidence: 96%
“…(54) has shown MIC of 12.5 μg/mL [75]. In continuation, a series of di/trisubstituted pyrazolo [3,4-d]pyrimidines (55,56) were observed no significant anti-TB activity at concentrations up to 6.25 μg/mL. A series of N,S-bis-alkylated thiopyrazolo [3,4-d]pyrimidines, based on sequential S-then N-alkylation, is carried out.…”
Section: A Series Of N-phenyl-6-methyl-2-oxo-4-phenyl-1234-tetrahydromentioning
confidence: 99%
See 1 more Smart Citation
“…A series of nitrofuran derivatives ( Figure 6) have been tested against Mtb H37Rv [39]. One compound in this series has shown excellent minimum inhibitor concentration (MIC) value 0.025 μg/mL, which is comparable to that of the frontline anti-tubercular agents like isoniazid and ethambutol.…”
Section: Nitrofuranyl Amidesmentioning
confidence: 99%